Optimalisasi Soft skill Melalui Digitalisasi dan Motivasi: Strategi Meningkatkan Kesiapan Kerja di Kalangan Mahasiswa - Emilda Oktavia; Ike Kusdyah Rachmawati; Theresia Pradiani (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2026)
This study examines the impact of soft skills, fieldwork practices or internship (PKL), and digitalization on work motivation and job readiness among students in Malang, addressing the challenges of competency gaps in the global labor market. Using a quantitative approach, data were collected via questionnaires from 260 students with experience in PKL or soft skills training. The results reveal that soft skills significantly enhance work motivation and job readiness directly, while work motivation is shown to be a primary driver of job readiness. Although PKL and soft skills positively influence the enhancement of digital competencies, this digital transformation does not have a direct impact on job readiness. PKL contributes to strengthening digitalization but does not directly affect motivation or job readiness. Key findings highlight the highly effective mediating role of work motivation in transforming soft skills into job readiness, whereas mediation through digitalization is not significant. This indicates that the development of soft skills and strategies to enhance work motivation are more crucial for job readiness than isolated interventions of digitalization or PKL. Consequently, higher education institutions need to design curricula that integrate continuous soft skills training, strengthen motivational mentoring programs, and optimize fieldwork practices with an emphasis on professional attitude development. This research provides important contributions to the development of human resource management theory and higher education practices in preparing adaptive graduates.